Reporting of Non-Financial Performance Indicators – a Useful Tool for a Sustainable Marketing Strategy - Adriana Calu; Costel Negrei; Daniela Artemisa Calu; Viorel Avram (Amfiteatru Economic Journal, 2015)
The current research has as objective to identify the reporting practices of non-financial information through the indicators proposed by the Global Reporting Initiative (GRI) and the degree in which, for marketing purposes, there is a preference for the communication on positive aspects. In this respect we used the information published into the non-financial reports of 19 organizations that had adhered to the pilot programme of the International Integrated Reporting Council (IIRC). We selected a number of 30 environment and social indicators reflecting both positive and negative aspects, and we analysed the manner in which they are presented within the reports published by the organizations, following the activities to be taken into consideration for the development of a sustainable marketing strategy: supply - production - distribution. The results of the study emphasized the fact that, regardless of the sector where the organizations run their activity, though there is no homogenous display, they report mainly the indicators presenting positive information 53 %), whereas the indicators presenting negative information are reported only in proportion of 33%. The organizations holding information regarding suppliers' sustenability emphasize this aspect in order to create a brand value whereas the rest of the organizations state that they shall proceed to such evaluations in the future. Interpreting these results through the agency of the institutional theory leads to the conclusion that certain organizations' option to voluntarily report according to a certain referential is carried out mainly in order to obtain rightfulness. Moreover, the sustainable conduct adopted by the main market competitors generates a mimetic-type isomorphism.
Keywords: M31; Q52; M49; 330; sustainable marketing; sustainability; sustainability reports; non-financial indicators; GRI; institutional theory